FoxO3a reactivation restores the sensitivity to the antiestrogen treatment in tamoxifen resistant breast cancer - Donà, Ada Alice; Andò, Sebastiano; Sisci, Diego (My University, 2017)
Resistance to endocrine treatments is a major clinical challenge in the management of estrogen receptor alpha positive (ER+) breast cancers (BC). Although multiple mechanisms leading to endocrine resistance have been proposed, the poor outcome of this subgroup of BC patients demands additional studies. Here we show that the expression of FoxO3a transcription factor is strongly reduced in ER+ BC MCF-7 cells (wtMCF-7) that developed resistance to Tamoxifen (TamR). On the other hand, FoxO3a silencing (siF3a) was able to counteract Tam induced growth inhibition in wtMCF-7, demonstrating that FoxO3a is a mediator of cell response to Tam. To analyze the role of FoxO3a in the acquisition of a Tam resistant phenotype, TamR clones bearing an active FoxO3a (F3aAAA), whose expression can be induced by Doxycycline (Dox) were developed. FoxO3a re-activation was able to re-establish the sensitivity of TamR cells to the antiestrogen, inhibiting proliferation and cell cycle progression, as well as restoring Tam dependent apoptotic response. For a closer look at the molecular mechanisms involved, an unbiased proteomics analysis on F3aAAA-inducible TamR cells was conducted, unveiling novel interesting and potential mediators of the anti-proliferative and pro-apoptotic activity of FoxO3a, all worthy of future investigations. Kaplan-Meier (K-M) survival curves confirmed the relevance of FoxO3a also in a clinical setting, since high levels of the transcription factor strongly correlate to a positive response to tamoxifen therapy. Finally, to assess if FoxO3a reactivation is able to restore the sensitivity to Tam also in vivo, the widely used anti-epileptic drug (AED) Lamotrigine (LTG; Lamictal), which is able to induce FoxO3a expression in TamR cells leading to growth inhibition, was also tested on TamR deriving xenografts tumors, where it showed the same effects observed in vitro. Altogether, our data indicate that FoxO3a could not only be considered a good prognostic factor in ER+ BC, predicting a positive response to endocrine therapy, but also a key target to be exploited in combination therapy. In this context, LTG might represent a valid candidate to be used as an adjuvant to Tam therapy in patients at risk.
Dottorato di Ricerca in Medicina Traslazionale. Ciclo XXIX
Keywords: Tamoxifen; Breast-Cancer